2015
DOI: 10.1089/cap.2014.0164
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Youth with Early-Phase Schizophrenia-Spectrum Disorders and Psychosis Not Otherwise Specified Treated with Second-Generation Antipsychotics: 12 Week Results from a Prospective, Naturalistic Cohort Study

Abstract: Objectives: The purpose of this study was to assess differences in the outcomes of youth with schizophrenia-spectrum disorders (SCZ-S) and psychotic disorder not otherwise specified (PsyNOS) during early antipsychotic treatment. Methods: The study was a prospective, naturalistic, inception cohort study of youth £ 19 years old with SCZ-S (schizophrenia, schizoaffective disorder, schizophreniform disorder) or PsyNOS (PsyNOS, brief psychotic disorder) and £ 24 months of lifetime antipsychotic treatment receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
(61 reference statements)
0
4
2
Order By: Relevance
“…We observed higher admission rates in the group with an index diagnosis of psychosis NOS compared to schizophrenia spectrum disorders, contrasting with previous evidence (Vernal et al, ). Psychosis NOS has low diagnostic stability, and approximately one‐third of people diagnosed with psychosis NOS are eventually diagnosed with schizophrenia (Fusar‐Poli et al, ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We observed higher admission rates in the group with an index diagnosis of psychosis NOS compared to schizophrenia spectrum disorders, contrasting with previous evidence (Vernal et al, ). Psychosis NOS has low diagnostic stability, and approximately one‐third of people diagnosed with psychosis NOS are eventually diagnosed with schizophrenia (Fusar‐Poli et al, ).…”
Section: Discussioncontrasting
confidence: 99%
“…We observed higher admission rates in the group with an index diagnosis of psychosis NOS compared to schizophrenia spectrum disorders, contrasting with previous evidence (Vernal et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…These studies suggest, however, that patients with PNOS have less severe psychotic symptoms and better short-term outcomes than patients with SZ (16,17). The findings are supported by studies examining PNOS in youths (18)(19)(20). In addition, patients with PNOS appear to have fewer psychotic episodes, shorter durations of illness and better functioning than participants with SZ, according to a larger study comparing all 12 DSM-IV psychotic disorders (3).…”
Section: Introductionmentioning
confidence: 93%
“…In a recent study of the use of atypical antipsychotic medications with child and adolescent psychiatric patients being treated in Spain, Baeza et al [31] reported that Risperidone was the most widely prescribed medication not only for youth with Schizophrenia Spectrum Disorders and Psychosis, Not Otherwise Specified, but also for Disruptive Behavior Disorders. In a very recent study of the 12 week results of the treatment of adolescents with Schizophrenia Spectrum Disorder and Psychosis Not Otherwise Specified, Vernal et al [32] compared Resperidone, Olanzapine, Aripiprazole, Quetiapine, and Ziprasidone. They reported that there were significant improvements with the clinician's choice of medication among both groups of patients, but there were also high rates of discontinuance among both groups.…”
Section: Need For Research On Medicationmentioning
confidence: 99%